How many feet lower is-282 than -68

Answers

Answer 1
Answer: Your equation is

-282 - (-68) =

when you subtract a negative, you "take away" that negative from the other value. The net result of that is adding the number. So the rule is minus negative means plus positive.

-282 - (-68) =
-282 + 68 = -214
Answer 2
Answer: -282 is -214feet than -68

Related Questions

100 to 150? Need this before midnight!
Compare the two functions give. explain which function has the greater rate of change
The number of blueberry muffins that a baker makes each day is 40% of the total number of muffins she makes.Part A:On Monday the baker makes 36 blueberry muffins. What is the total number of muffins that the baker makes on Monday?Part B:On Tuesday, the baker makes a total of 60 muffins. How many blueberry muffins does the baker make on Tuesday?Once again please answer this question ASAP and please explain! Thanks!
Nine thousand, six hundred five and nine tenths
What is 357 divided by (-7)

Jim & Jesse each had the same amount of money. Jim spent $58 and Jesse spent $37. Afterward, the ratio of Jim's money to Jesse's is 1:4. How much money did each have at first?

Answers

x-\ money\ that\ each\ of\ them \ had\ previously\n\n4(x-58)=x-37\n\n4x-232=x-37\ \ \  | subtract\ x\n\n3x-232=-37\ \ \ | add\ 232\n\n3x=195\ \ \ | divide\ by\ 3\n\nx=65\n\nEach\ of\ them\ had\ 65\$\ at\ the\ beginning.

While drying, apple loses 14% of its weight. How many pounds of fresh apple is needed to get 10 8/25 lbs of dried apple?

Answers

Answer:

Total fresh apple needed = 12

Step-by-step explanation:

It is given that, While drying apple loses 14% of its weight

To find the fresh apple needed

Let x be the total fresh apple needed.

Apple loses 14% of its weight. Final we need 10 8/25 lbs of dried apple

x - 14x/100 = 10 8/25

0.86x = 10 8/25

0.86x = 258/25 = 10.32

x = 12

Answer:

12lbs

Step-by-step explanation:

let x be the amount of apples you need, then:

x-0.14x= 10 8/25

0.86x = 10 8/25

(10 8/25) : 86 * 100 = x

x=12

What is the value of the function y=3x−1 when x =−1 ?−8

−4

2

6

Answers

So check my calculations,
Plug in -1 into the first equation as x
y= 3(-1)-1
y=-3-1
y=-4
Hope I helped! Do not hesitate to ask any questions :)

Is the relationship a function? (2.4) (2.5) (2.6) (2.7)

Answers

I believe this relationship would be a function then since all the x-values are different .

Is this congruent triangle SSS or SAS??? Please help!

Answers

There's no information in the drawing about any angles at all, so it can't be SAS.

It IS SSS, because two pairs of sides are marked congruent, and the same line 'EG'
is a side of both triangles.

Answer:

sss

Step-by-step explanation:

Is this right?
plz tell me

Answers

Yes it is correct... shifted UP is the key word
Yes up means adding